The oligosaccharides of alginate and chitosan influence the growth, metabolism and physiological processes in rice seedling: Oligosaccharides influence the rice seedling - Samdurkar, Anish N; Choudhary, Arvind D; Varshney, Lalit; Badere, Rupesh S (ORYZA-An International Journal of Rice, 2026)
Natural biostimulants such as alginate and chitosan oligosaccharides have emerged as promising tools for improving plant growth and stress tolerance. The study was undertaken to evaluate the effects of irradiated alginate and chitosan oligosaccharides on the growth, physiological attributes, and enzymatic activities of young rice plants. Seven-day-old rice seedlings were treated with different concentrations of alginate and chitosan oligosaccharides generated through gamma irradiation at varying doses. Among the treatments, alginate oligosaccharide produced at 500 kGy and applied at 200 ppm (A/500/200) proved most effective in enhancing biomass accumulation, photosynthetic performance, leaf water status, and the activities of enzymes associated with carbon metabolism and plant defence. Likewise, chitosan oligosaccharide produced at 200 kGy and applied at 400 ppm (C/200/400) significantly improved biomass production and enhanced seedling water relations. The yield improvement may be mediated through enhanced carbon assimilation, metabolic activity, and activation of defence-related enzymes. These findings highlight the potential of irradiated alginate and chitosan oligosaccharides as sustainable biostimulants for improving early-stage rice growth, physiological